PENGARUH MODAL INTELEKTUAL TERHADAP INOVASI PELAYANAN PUBLIK DESA: CUSTOMER CAPITAL SEBAGAI VARIABEL KUNCI - Deky Hamdani; Fadli Anugrah; Efrianto Efrianto (Gapenas Publisher, 2026)
This study aims to analyze the influence of intellectual capital on village public service innovation by positioning customer capital as the key variable. The low quality of service innovation at the village level is a relevant issue given the ongoing era of decentralization and government digitalization. The research approach uses a quantitative survey method with Structural Equation Modeling (SEM) analysis based on Partial Least Squares (PLS). The sample consisted of 215 village officials and 320 service-recipient residents, selected through proportionate stratified random sampling from 42 villages across three regencies in Sungai Penuh City. The results show that: (1) human capital has a positive and significant effect on public service innovation (? = 0.324; p < 0.01); (2) structural capital has a positive and significant effect (? = 0.287; p < 0.05); (3) customer capital has a positive and significant effect as a mediating variable (? = 0.412; p < 0.001); and (4) intellectual capital simultaneously influences village public service innovation (F = 47.32; p < 0.001). Customer capital is proven to be the most dominant variable in driving village public service innovation, reflecting the importance of relationships, trust, and community participation in the village service ecosystem. These findings provide theoretical and practical implications for the development of service innovation policies in village governance.